The relationship of vegetable and fruit consumption to mental health in adolescents and early adults: Scoping review - Reiza Dwi Yuniar; Shafira Dwiva Rochmi; Almira Sitasari; Agus Wijanarka; Tri Siswati (DAPU Aceh Publishing, 2025)
Mental disorders in adolescents have an adverse impact on their academic performance, lifestyle, and quality of life. Consumption of fruits and vegetables is important to maintain good physical and mental health. The aim is to determine the effect of vegetable or fruit consumption on mental health in adolescents. The research method was scoping review of journals obtained through databesed electronic media, namely Pubmed and google scholar. the results of the study were 8 articles found a relationship between the effect of vegetable or fruit consumption on mental health in adolescents while 1 journal showed no effect between consuming vegetables and fruit with mental health. The conclusion of the study is that vegetable and fruit consumption has an influence on mental health. This mental health such as, symptoms of depression, mood, loneliness, anxiety etc.